2018
DOI: 10.1002/aenm.201802832
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Large‐Area Organic Solar Cells Enabled by Sequential Bilayer Processing via Nonhalogenated Solvents

Abstract: power conversion efficiency (PCE) of BHJ devices strongly depends on phase separation of the donor and acceptor. However, the formation of BHJ morphology is an extremely complicated process and the formed morphology is also a highly delicate balance involving many parameters such as domain size, purity, miscibility, etc. To achieve high-performance devices, much effort has been devoted to delicately control the morphology of the active layer (such as the blend ratio between the donor and acceptor, [9][10][11] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
161
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 41 publications
2
161
0
Order By: Relevance
“…2019, 9,1900044 an almost comparable PCE with those of the devices fabricated by the spin coating method. [54,55] In addition, as expected results via the spin coated devices, the printed photoactive layer exhibits a homogeneous and smooth surface morphology with a small RMS roughness of 1.99 nm even at the thickness of ≈300 nm ( Figure S11 (see Figures 8c and 3a,c). Based on this study, we found that the morphology of the photoactive layer is strongly dependent on the inherent properties of m-ITIC-Rs.…”
Section: Printed Opv Devices Fabricated With the Doctor Blade Methodssupporting
confidence: 77%
“…2019, 9,1900044 an almost comparable PCE with those of the devices fabricated by the spin coating method. [54,55] In addition, as expected results via the spin coated devices, the printed photoactive layer exhibits a homogeneous and smooth surface morphology with a small RMS roughness of 1.99 nm even at the thickness of ≈300 nm ( Figure S11 (see Figures 8c and 3a,c). Based on this study, we found that the morphology of the photoactive layer is strongly dependent on the inherent properties of m-ITIC-Rs.…”
Section: Printed Opv Devices Fabricated With the Doctor Blade Methodssupporting
confidence: 77%
“…However, such a method is unable to separate the donors and the acceptors, the vertical phase separation of the active layers are still not well regulated. There are also related literature reporting the use of orthogonal solvents or simultaneously citing a third solvent to increase the donor and the acceptor contact areas, and achieve higher efficiency whereas the choice of orthogonal solvents and device preparation process are more complicated 31–35. By summarizing the advantages and disadvantages of the above literature, we can find that when donor and acceptor materials were dissolved using nonorthogonal solvents, the processing of the films were well completed which can also regulate vertical phase separation well 36.…”
Section: Introductionmentioning
confidence: 99%
“…However, the citing a third solvent to increase the donor and the acceptor contact areas, and achieve higher efficiency whereas the choice of orthogonal solvents and device preparation process are more complicated. [31][32][33][34][35] By summarizing the advantages and disadvantages of the above literature, we can find that when donor and acceptor materials were dissolved using nonorthogonal solvents, the processing of the films were well completed which can also regulate vertical phase separation well. [36] Therefore, it is feasible to construct a bilayer active layer by sequential spin-coating.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although it is highly challenging, achieving highly efficient NFOSCs by using environmental friendly solvent would have profound impacts in the research field. [6,[40][41][42][43][44] Herein, we designed and synthesized a novel building block methyl 2,5dibromo4fluorothiophene3carboxylate (FET), a monothiophene functionalized with both fluorine (F) atom and ester (E) group. FET was copolymerized with BDT to afford a new polymer donor P1 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%